Implementasi Digital Marketing pada Pengrajin Tas Anyam Desa Pesidi Kecamatan Grabag, Kabupaten Magelang - Nur Hidayah; Irfan Maulana; Seto Priyambodo Suryawan; Siti Nur Halimatus Sa’diah; Sita Indriyani; Latifur Rizka (University of Merdeka Malang, 2021)
People in Pesidi village have an additional livelihood as woven bag craftsmen. Many housewives become craftsmen because the production time is flexible and can be done at home. However, the problems faced by woven bag craftsmen include the lack of product innovation, conventional sales systems, low selling prices resulting in low income, craftsmen not having knowledge of digital marketing, and inventory buildup due to lack of sales. The purpose of this community service is to increase digital marketing knowledge and reduce the problems of woven bag craftsmen. The methods used are socialization to local government and craftsmen, training (lectures, simulations, and discussions), and assistance in making digital marketing. The results of the service are in the form of marketing innovation through digital marketing, an increase in income of 7%, an increase in the understanding of woven bag craftsmen about digital marketing, and product sales with an online system via email, Facebook, Instagram, and market places available on digital platforms.